convert to vertex form y=-2x^2+6x+1 and y=x^2+4x+1
- print Print
- list Cite
Expert Answers
calendarEducator since 2011
write5,348 answers
starTop subjects are Math, Science, and Business
You need to remember what the vertex form of a quadratic is such that:
`y = a(x-h)^2 + k`
Notice that (h,k) expresses the vertex of parabola.
The problem provides the equation `y=-2x^2+6x+1` , hence you should collect the terms `-2x^2+6x` , to factor out -2 and to complete the square`x^2 - 3x` such that:
`x^2 -...
(The entire section contains 169 words.)
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Related Questions
- `y=2x^2+4x-3` Find the vertex and intercepts.
- 2 Educator Answers
- How we simplify 2x/(x^2 -6x+9) - 1/(x+1) - 8/(x^2 -2x-3)
- 2 Educator Answers
- How convert a cubic equation in standard form ax^3+bx^2+cx+d to vertex form a(x-h)^3+kI need...
- 1 Educator Answer
- convert (x^3)-(4x^2)+x+26 into vertex form
- 1 Educator Answer
- Evaluate the integral integrate of ((6x^2-2x-1)/(4x^3-x))dx
- 1 Educator Answer
=x^2+4x+1
= (x^2+4x)+1
divide the coefficient of x(4) by 2'then suare it
= [x^2+4x+(4/2)^2]+1 that is [(4/2)^2=2^2=4]
=(x^2+4x+4-4)+1
= (x^2+4x+4)-4+1
=(x^2+2)-3
This is another method of coverting quaratic equations to vertex form.
the questions can be solved using completing the square method.
Student Answers